Privatisasi Komunikasi dan Demokrasi - Putra, I Gusti Ngurah (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
Democray as communicative action involving the ruler and ruled is underthread by the increasingly popular ide of mass media privatization. The supposedly efficent mode of marked-based system, in fact, fails to satisfy the need to facilitate peoples actualization of their citizenship rights, and enhancing their communicative competence. The idea of citizenship is replace by customer service for the sake of capital accumulation and control.